The effects of Curcuma xanthorrhiza rhizome simplicia and Camellia sinensis green tea in a patient with chronic hepatitis B infection: a case report - Ismail, Sjarif; Fikriah, Ika; Tandirogang, Nataniel; Kosala, Khemasili (Indonesian Journal of Pharmacology and Therapy, 2022)
The hepatitis B virus (HBV) causes acute and chronic liver infections which can be treated by using interferon and antiviral. However, the treatment is relatively expensive. We reported here a case of a patient with chronic hepatitis B who had negative seroconversion without interferon (IFN) and antiviral treatment after herbal consumption. A retrospective investigation showed that the patient consumed Curcuma xanthorrhiza rhizome and Camelia sinensis green tea. These herbs were widely both in vitro and in vivo studied for their effects against HBV infection, although the clinical studies are limited. This case reported the effect of C. xanthorrhiza rhizome and C. sinensis green tea consumption in a patient with chronic hepatitis B. A female patient with chronic hepatisis B infection at the age of 32 y.o. had been taking neuro vitamins regularly for a year before infection detected. She was an asymptomatic patient with normal limits liver function, positive HBsAg and negative anti-Hbs. At the age of 45, she started taking C. xanthorrhiza rhizome simplicia equivalent to 5mg of curcumin twice daily and drinking C. sinensis green tea regularly. Six years later, HBsAg was not detected and her liver function remained within normal limits and Anti-HBs were detected 5 years later. In conclusion, the consumption of C. xanthorrhiza rhizome and C. sinensis green tea can against chronic hepatisis B infection by eliminate HBV dan induce anti-HBs.